Effects of indoor lighting environments on paper reading efficiency and brain fatigue: an experimental study - Zhou, Anqi; Pan, Younghwan (Frontiers in Built Environment, 2023)
This study investigated the influence of indoor lighting environments on paper reading efficiency and brain fatigue to explore lighting parameters that benefit users during various reading durations. The study was conducted in the Smart Lighting Lab, where 12 participants were tested under different illuminance levels and correlated color temperatures (CCT) for three distinct reading durations. Reading efficiency during the task tests and objective measures of brain activity by monitoring participants' electroencephalograms (EEGs) were used as key factors to assess participants' fatigue levels. By analyzing the subjective and objective results, we found that paper reading efficiency was significantly affected by changes in the lighting environment. Also, based on the results of this study, we propose lighting recommendations for paper reading tasks of different durations. For a 15-minute reading task, the lighting condition of 500 lux-6500 K were the most efficient for reading; for a 30-minute reading task, 500 lux-4000 K lighting environments were found to be the most effective; and 750 lux-6500 K was the best lighting environment for a 60-minute reading duration. These suggestions can serve as a reference for designing indoor lighting environment. In addition, they provide guidance to researchers and reviewers conducting similar studies.